A Sequential Explanatory Mixed Methods Study of Young Adult Tobacco and Marijuana Co-Use. (10th November 2019) - Seaman, Elizabeth L.; Howard, Donna E.; Green, Kerry M.; Wang, Min Qi; Fryer, Craig S.
Abstract: Background: The co-occurring use of tobacco and marijuana among young adults is an important behavioral phenomenon within the field of substance use. Studying tobacco and marijuana use together among young adults can provide important insight into patterns of initiation and continuation. Objectives: The primary goal of this study was to examine characteristics associated with co-use among young adults and to discover the ways experiences of co-users can help contextualize trends in co-use. Methods: This study employed a sequential explanatory mixed methods design. Quantitative analyses used 12 years of nationally representative National Health and Nutrition Examination Survey (NHANES) data (2005–2016) to assess the characteristics and experiences of young adult (21–30) co-users. Results from analyses of NHANES, prior literature, and theoretical constructs were used to develop a guide for 20 in-depth, semi-structured interviews with young adult co-users living in the state of Maryland. Interviews were analyzed using thematic analysis. Quantitative results and qualitative findings were integrated. The original NHANES analysis occurred during October and November 2017, interviews took place during December 2017 and January 2018, and all mixed methods integration was conducted in 2018. Results: Tobacco and marijuana co-users have unique characteristics and experiences compared to single product users; the experiences of co-users can offer unique insights on co-use. Meta-inferences emerged from integration. Conclusions/importance : Co-users conceptualize tobacco and marijuana differently and hold different risk perceptions for each substance. Co-users may be at risk for polytobacco product use. These findings highlight the profound influence these two substances have on young adult co-users' experiences and behaviors.